2022
DOI: 10.1371/journal.pone.0264699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmacovigilance systems for reporting medication errors in Africa and the role of patients using a mixed-methods approach

Abstract: Background Reviewing the epidemiological profile of medication errors (MEs) reported by African countries and the systems put in place to report such errors is crucial because reporting plays an important role in improving patient safety. The objectives of this study were to characterize the profile of spontaneously reported MEs submitted by African countries to VigiBase; the World Health Organization (WHO) global database of individual case safety reports, describe systems in place for reporting these errors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…An earlier study found limited systems in African countries for patients to report these errors for appropriate action. 34 To prevent medication errors, caregivers in our study have adopted tools and support systems that were found to reduce these errors as shown in an earlier study. 5 …”
Section: Discussionmentioning
confidence: 98%
“…An earlier study found limited systems in African countries for patients to report these errors for appropriate action. 34 To prevent medication errors, caregivers in our study have adopted tools and support systems that were found to reduce these errors as shown in an earlier study. 5 …”
Section: Discussionmentioning
confidence: 98%
“…In countries where the patient reporting system is well established and effective, it noted that raising awareness among patients/consumers about the significance of reporting and encouraging their participation in medication safety are crucial to the success of the program [ 21 ]. In addition, a lack of knowledge, difficulty with reporting procedures, and a lack of feedback have been cited as bottlenecks in consumer reporting [ 6 , 16 ]. The findings necessitate the use of various available platforms, including social media, television, and radio to educate the public and consumers regarding PV and the importance of reporting ADRs [ 5 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In developed countries, consumer/patient reporting systems started in the 1960s, however, the practice is new in low-middle-income countries [ 15 ]. In many countries, lack of resources and financial constraints has been associated with the poor promotion of consumer reporting systems [ 6 , 12 , 16 ]. Reported barriers to ADR reporting include lack of interest, reluctance, complacency, ignorance, and lack of incentives [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation